Color in Medieval Castle Architecture in Present-Day Poland and Czech Republic - Adamska, Dagmara; Nocuń, Przemysław; Ratajczak, Tomasz; Záruba, František (MDPI, 2022)
Colors were ubiquitous in the medieval world, and castles were no exception. While in the eyes of most people their rich color schemes manifested power and wealth, some could also read the more nuanced messages these colors conveyed. The main objective of this paper is to discuss the use and role of color in the interiors of castles of medieval Bohemia and Poland. The picture is complemented by the analysis of color decorations of defensive residences of the Teutonic Order. The discussion takes into account the varying states of preservation and draws from the available written accounts. To present the most complete picture possible, we discuss royal residences, for whichunfortunately limited data are available, as well as the better-preserved castles of dukes and knights.We discuss the identified iconographic programs and their chivalric, heraldic, and hagiographicmotifs. Within the scope of our discussion are late forms of floral decorations, known as “greenchambers”. The numerous examples presented in the paper prove that color was an important tool of visual social communication in castle architecture: it complemented the symbolism, and sometimescarried an independent message.
Keywords: zamki (architektura); malarstwo; kolory; dekoracje; Polska; Czechy